Contributions of Vibronic Couplings to Photoelectron Spectroscopy in a Dimer: The Case of an Organic Mixed-Valence System (Communications in Computational Chemistry, 2025)
In the framework of a dynamic vibronic model, we report the influence of both local and nonlocalvibronic coupling on the vibronic energy levels for organic mixed-valence systems, and then evaluatetheir contributions to photoelectron spectroscopy of a realistic molecule as an example. Our resultsdemonstrate that the variation of nonlocal vibronic coupling constant in the dimeric model doesn’tinfluence the relative positions of vibronic energy levels. For the spectrum simulated, it tries to maintainthe constant difference $2t^0_{ab}$ between the splitting energy levels corresponding to two peaks of the first ionizations.